Management of development of facilities and infrastructure in the implementation of School-Based Management (Qualitative Descriptive Analysis of MAN 2 Palembang City) - Mediwinata, Ahmad Fadil (Magister PAI Universitas Singaperbangsa Karawang, 2025)
This research was conducted at MAN 2 Palembang City, which was selected purposively with the aim of analyzing the results of research findings related to planning, implementation, supervision, obstacles and efforts to overcome obstacles in the development of facilities and infrastructure in schools. In this study, the author used a descriptive analysis method that began with the stages of data collection in the form of observation, interviews and documentation. So that various types of data related to the research problem were collected, then verification of the validity of the data using triangulation techniques. Then the author conducted data analysis and interpretation to find answers to the problems raised in this study. From the results of the research conducted, the answers obtained were that: (1) School-Based Management is interpreted as the transfer of decision-making from the central level to the school level, (2) planning for the development of infrastructure facilities begins with analyzing needs, conducting surveys, selecting primary needs and developing educational specifications, (3) implementation of infrastructure development is carried out through assistance from the school committee, parents of students and the government, (4) supervision of infrastructure development is carried out through direct and indirect approaches, (5) obstacles faced in the development of facilities and infrastructure are the low involvement of business people in the educational environment, the unequal distribution of managerial skills of school committees, the unequal distribution of parent and community competencies, the low involvement of students in the process of maintaining school infrastructure facilities, (6) efforts made to overcome obstacles in the development of infrastructure facilities are personal development, improving management quality, building initial commitment from parents and prospective students, and establishing cooperation with other schools/institutions.